A retrospective medical chart review of clinical outcomes in children and adolescents with attention-deficit/hyperactivity disorder treated with guanfacine extended-release in routine Canadian clinical practice - Judy van Stralen; Simerpal K. Gill; Christopher J. Reaume; Kenneth Handelman (BMC, 2021)
Abstract Objective This study evaluated clinical outcomes in children and adolescents with attention-deficit/hyperactivity disorder (ADHD) treated with the α2-adrenoceptor agonist guanfacine extended-release (GXR) in routine Canadian clinical practice. Methods This retrospective chart review focused on patients with ADHD aged 6-17 years initiating treatment with GXR as monotherapy or adjunctive therapy. Patients were followed for up to 12 months after GXR initiation and, if they had received prior ADHD pharmacotherapy, for 12 months before GXR initiation. The primary outcome was change in ADHD symptoms and functionality based on physician assessments, classified as improvement, no change, or worsening relative to the time of GXR initiation. Treatment-emergent adverse events (TEAEs) were evaluated. Clinical outcomes were also analyzed post hoc according to whether GXR treatment was received as monotherapy or adjunctive therapy, and by select psychiatric comorbidities. Exploratory analyses were conducted in patients who had received prior ADHD pharmacotherapy to evaluate clinical outcomes after initiating GXR. Results Improvements in ADHD symptoms were reported for 232/330 (70.3%) patients. Functional improvements in school performance and home life were reported for 213/330 (64.5%) and 209/330 (63.3%) patients, respectively. The most frequent TEAEs (≥ 5%) were somnolence, headache, insomnia, presyncope, and decreased appetite. Improvements in ADHD symptoms were observed when GXR was received as either monotherapy (35/60 [58.3%]) or adjunctive therapy (197/270 [73.0%]). Improvements in ADHD symptoms and functionality were observed in the majority of patients with select psychiatric comorbidities. Among patients who had experienced worsening of symptoms with prior ADHD pharmacotherapy, 44/54 (81.5%) experienced symptom improvement, 33/44 (75.0%) who had previously experienced worsening of school performance improved, and 34/48 (70.8%) who had previously experienced worsening of home life improved. Conclusion In Canadian routine clinical practice, most children and adolescents with ADHD treated with GXR experienced improvements in ADHD symptoms and in functionality both at school and at home.